Paperworks : colorful crafts from picture eggs to fish kites - Fowler, Virginie (Englewood Cliffs, N.J. : Prentice-Hall, 1982)
Presents a variety of projects including jewelry, toys, and holiday decorations, made from paper using such techniques as collage, papier maché, printing, and various types of cutting and construction. Includes step-by-step illustrated instructions.
Includes index.
Keywords: Paper work -- Juvenile literature; Paper work; Handicraft